Strategies for Promoting Energy Literacy in Physics Education: Insights from a Systematic Literature Review - Sriatun, Neng; Ardianto, Didit; Irvan Permana; Afriana, Jaka (Universitas Negeri Semarang, 2025)
In physics education, fostering energy literacy is essential to equip students with the skills needed to navigate resource scarcity and environmental issues. By developing energy literacy, students are better prepared to manage energy consumption in a sustainable and sustainable manner. This research aims to explore effective strategies and approaches to improve students' energy literacy through the Systematic Literature Review (SLR) method. The study analyzed academic papers from reputable sources such as ScienceDirect, Taylor & Francis, Springer Nature, and ERIC, with a focus on publications from 2020 to 2024. Using keywords such as